Who Wins, Who Loses? Understanding the Spatially Differentiated Effects of the Belt and Road Initiative - Lall, Somik V.; Lebrand, Mathilde (World Bank, Washington, DC, 2019)
This paper examines how cities and regions within countries are likely to adjust to trade openness and improved connectivity driven by large transport investments from China's Belt and Road Initiative. The paper presents a quantitative economic geography model alongside spatially detailed information on the location of people, economic activity, and transport costs to international gateways in Central Asia to identify which places are likely to gain and which places are likely to lose. The findings are that urban hubs near border crossings will disproportionately gain while farther out regions with little comparative advantage will be relative losers. Complementary investments in domestic transport networks and trade facilitation are complementary policies and can help in spatially spreading the benefits. However, barriers to domestic labor mobility exacerbate spatial inequalities whilst dampening overall welfare.